MENINGKATKAN KEMAMPUAN BERHITUNG PADA ANAK USIA DINI MELALUI METODE BERNYANYI - Karnida, Karnida; Rodiana, Dina; Komala, Komala (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
Counting is a part of mathematics, the goal is to develop numeracy skills that are needed in everyday life. The singing method is an activity that uses sound instruments that can add insight into things that are not yet known to the child and will get new words so that it can enrich the vocabulary and be more skilled at using it. The ability to count in early childhood in Nurul Amanah Kindergarten is still low. The purpose of this study was to obtain an overview of improving children's numeracy skills through the singing method. The study was conducted using the classroom action research method. The data of this study were collected through observation and documentation of collected data analyzed in description. From the results of this study we can conclude the results that the ability of early childhood counting of 16 children consisting of 9 men and 7 women in fact has increased, this is taken from the final results after the implementation of actions in cycle 2 which is clear from each - the number of children in the category began to grow by 5 people, which was in the category of developing very well 7 people and in the category of developing very well as many as 4 people.